THE LEGAL STATUS OF AN ECOLOGICAL DISTRICT (Journal of actual problems of jurisprudence, 2019)
At the moment, the implementation of the ecological area in practice causes many difficultiesmethodological, methodological and organizational nature. Not developed theoreticallya well-founded concept, the place and role in the system of territorial planning andmanagement and the technique of ecological zoning is not developed.